Assessment of relationship between land uses of riparian zone and water quality of river for sustainable development of river basin, A case study of U-Tapao river basin, Thailand - Saroj, Gyawali (2016)
The main objective of this study is to find the relationship between land use patterns of riparian zone of the river and water quality parameters. Various water quality parameters were collected from 10 monitoring stations of U-tapao River in the year 2000 to 2011 as secondary data. Land use data as the percentage of land of 100 m riparian zone along the river network were derived from using Geographical Information Systems (GIS) and they were linked with water quality data. Analysis of variance, correlation analysis and stepwise multiple regression analysis were used to investigate spatial and temporal variations and the interrelationships between land uses and water quality parameters. Water quality parameters: temperature (TEMP) and dissolved oxygen (DO) showed spatial variation, whereas TEMP,suspended solid (SS) and fecal coliform bacteria (FCB) showed seasonal variation. Land uses: agriculture, urban, and grass land showed spatial variation, whereas only agriculture and grass land showed annual variation. Urban land showed significant positive correlation with TEMP, SS and dissolved solid (DS) and negative correlation with pH. Similarly, agriculture showed significant positive correlation with SS and DS and negative correlation with TEMP and DO. In the study, water quality parameters were predicted by using multiple regression models and understanding of these relationships can help policy or decision makers to develop suitable land use practices on the riparian zone for sustainable development of a river basin.